A psychometric evaluation of the Chinese Impact of Vision Impairment (C-IVI) questionnaire in an adult cohort with high myopia using Rasch analysis - Wei Pan; Ryan E. K. Man; Eva K. Fenwick; Ziqi Hu; Yanfeng Jiang; Huanhuan Tan; Zhongping Chen; Quan V. Hoang; Seang-Mei Saw; Ecosse L. Lamoureux; Weizhong Lan; Zhikuan Yang (PLoS ONE, 2025)
Purpose A psychometric evaluation of the Chinese Impact of Vision Impairment (C-IVI) questionnaire in an adult cohort with high myopia using Rasch Analysis and determination of the relationship between vision-related quality-of-life (VRQoL) and myopia macular degeneration (MMD). Methods We used the baseline visit data of the AIER-Singapore Eye Research Institute (SERI) High Myopia Adult Cohort Study. VRQoL was assessed using the 28-item C-IVI. Rasch analysis was conducted to evaluate the overall C-IVI and domain scores (‘Mobility and independence’—MB, ‘Reading and accessing information’—RD, and ‘Emotional well-being’—EWB), including response category functioning, precision, unidimensionality, targeting, and differential item functioning (DIF). The criterion validity, C-IVI’s ability to distinguish participants based on severity of vision impairment (VI), spherical equivalent (SER), and the presence of MMD were analyzed using ANOVA and pairwise t-tests. Results There were 431 participants, with mean (SD) age of 42.2 (7.1) years, SER of −8.3 (3.8) D, and visual acuity of 0.1 (0.2) LogMAR. Of these, 15.8% presented MMD, 79.4%, 13.5%, 7.0%, and 0.2% had no, mild, moderate, and severe VI, respectively. Response thresholds were ordered for the overall and three domains. The overall range-based precision was 0.94, and 0.80 for each domain. The three domains demonstrated unidimensionality. DIF was uniform in overall and EWB, but not the MB and RD domains. Person estimates decreased with increasing VI severity, worsening SER, and presenting MMD (all p < 0.05) for the overall and domain scores. Conclusions The C-IVI questionnaire is a valid and reliable tool for assessing VRQoL in adults with high myopia in China.